IHC versus FISH versus NGS to detect ALK gene rearrangement in NSCLC: all questions answered?. Issue 6 (22nd March 2021) - Batra, Ullas; Nathany, Shrinidhi; Sharma, Mansi; Pasricha, Sunil; Bansal, Abhishek; Jain, Parveen; Mehta, Anurag
Abstract : Aims: Anaplastic lymphoma kinase ( ALK ) rearranged non-small cell lung carcinoma (NSCLC) is a distinct molecular subtype and rapid approval of ALK tyrosine kinase inhibitors (TKIs) has necessitated rapid and sensitive diagnostic modalities for the detection of this alteration. Gene rearrangements can be identified using many techniques including fluorescence in situ hybridisation (FISH), reverse transcriptase-PCR, next-generation sequencing (NGS) and immunohistochemistry (IHC) for fusion oncoprotein expression. We aimed to determine the concordance between IHC, FISH and NGS for ALK biomarker detection, and determine differences in sensitivity, and survival outcomes. Methods: We analysed the concordance between IHC using D5F3 monoclonal antibody, FISH (break-apart) and NGS using a custom panel containing 71 different ALK variants. Results: Among 71 cases included in this study, FISH was evaluable in 58 cases. The concordance of ALK IHC with FISH was 75.9% and that with NGS was 84.5%. The sensitivities of FISH and NGS were 75.6% and 87.5%, respectively. The median progression-free survival of ALK IHC-positive and FISH-negative group was 5.5 months and that of both positive was 9.97 months. Conclusion: Although NGS offers a better throughput and visualisation, IHC still remains the quintessential screening tool in upfront diagnosis of ALK rearranged NSCLC.